1997
DOI: 10.1007/s004670050257
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of minerals, oxalate, and uric acid in north Indian children

Abstract: Urinary excretion of calcium, magnesium, phosphate, uric acid, oxalate, and creatinine was measured in 208 children (aged 8 -15 years, 124 boys, 84 girls), living in a residential school near New Delhi. Levels were reduced compared with those reported from developed countries. The 95th percentile value of 24-h creatinine excretion was 33.4 mg/kg, calcium 2.2 mg/kg, magnesium 2.9 mg/kg, phosphate 9.4 mg/kg, uric acid 4.4 mg/kg, and oxalate 1.5 mg/kg. The 95th percentile value of the urine calcium/creatinine rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 15 publications
3
30
1
Order By: Relevance
“…This finding was well corroborated with several previous studies [9,16,[19][20][21][22]. It also observed that for every age group, different urine Ca/Cr ratio was reported [3,8,23]. This difference may be due to exposure to sunlight, climate, genetics, nutritional habits, drinking water and ethnicity.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This finding was well corroborated with several previous studies [9,16,[19][20][21][22]. It also observed that for every age group, different urine Ca/Cr ratio was reported [3,8,23]. This difference may be due to exposure to sunlight, climate, genetics, nutritional habits, drinking water and ethnicity.…”
Section: Resultssupporting
confidence: 91%
“…The prevalence of idiopathic hypercalciuria (IH) has been reported to vary between 2.9% -6.2% in the age group of 3 months to 18 years [1][2][3][4][5][6]. The majority of these cases are asymptomatic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 A third group was from North India and again the value was quite low, with the authors' suggestion that this re£ected nutritional inadequacy in this population. 4 The fourth group was from Hungary in 1995 and was strikingly low throughout early childhood, a discrepancy that is unexplained. 6 These four groups were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Sweid et al [22], in 1997, reported data on 258 children of 8-15 years of age from North India. The daily urinary calcium excretion in this population was only 0.7 mg/kg with the 95th percentile at 2.2 mg/kg.…”
Section: -H Urinary Calcium Excretionmentioning
confidence: 99%